Biotin‐Appended Iron(III) Complexes of Curcumin for Targeted Photo‐Chemotherapy. Issue 17 (20th April 2021) - Sahoo, Somarupa; Raghavan, Abinaya; Kumar, Arun; Nandi, Dipankar; Chakravarty, Akhil R.
Abstract: Iron(III) complexes of curcumin (Hcur) having a tridentate NNN ‐donor dipicolylamine‐based ligand L 1 and its biotinylated analogue L 2, namely, [Fe(L 1 )(cur)Cl] (1 ) and [Fe(L 2 )(cur)Cl] (2 ), were prepared, characterized and their photo‐induced cytotoxicity studied. The complexes exhibited curcumin‐based absorption band near 430 nm and emission maxima at 520 nm. Complex 2 with a biotin moiety showed enhanced cellular uptake and higher cytotoxicity compared to its non‐biotin analogue 1 . The visible light induced cytotoxicity was studied in HeLa, MCF‐7 and HepG2 cell lines. Complex 2 displayed photodynamic effect (400–700 nm, 10 J cm −2 ) giving an IC50 value of ∼4 μM in HeLa and MCF‐7 cells, while being significantly non‐toxic in the dark (IC50 >100 μM). A 5‐fold increase in cytotoxicity was observed in HepG2 cells (IC50 ∼0.7 μM) for the biotin‐appended complex 2 . In vitro generation of reactive oxygen species (ROS) was observed from dichlorofluorescein diacetate (DCFDA) assay. The mode of cell death was apoptotic. Formation of hydroxyl radicals as the ROS was evidenced from the plasmid pUC19 DNA photo‐cleavage studies. The complexes demonstrated the ability to act as targeted PDT (photodynamic therapy) drugs. Abstract : Iron(III) complexes of curcumin, an active ingredient of turmeric, and a pendant biotin moiety showed high cellular uptake in HeLa cells and excellent photo‐cytotoxicity in HepG2 cells with apoptotic cell death by hydroxyl radicals as the reactive oxygen species generated on light activation, while the complex remained non‐toxic in dark.